"May balak ka bang magkaanak?" factors influencing selected Filipino Gen Z's desire to have children in the future - Daloria, Pamela Justine S.
The birth rate of the Philippines has been in a constant decline for the past 22 years. The country’s fertility rate has also dropped drastically in 60 years. Yet, studies that investigate childbearing desire among Filipinos are lacking. Hence, this study looked into the desire of selected generation Z Filipinos to have children in the future, the factors that affect their desire, and the circumstances that may change their intention. A researcher-made Childbearing Desire Questionnaire (CDQ) and in-depth interviews were utilized to gather data from 55 respondents. Quantitative data was subjected to descriptive statistics while qualitative data underwent thematic analysis. The results reveal that the majority of the respondents show no desire to have children in the future. Women displayed a higher desire to have children in the future while men reported higher uncertainty. Respondents with high personal income reported a greater desire to have children in the future. Meanwhile, those with low personal income reported less childbearing desire. Additionally, respondents who were in a relationship showed higher desire for childbearing. A low level of educational attainment was found to be connected with low childbearing desire. On the other hand, achieving an average level of education is connected to a higher desire to have children in the future. Happiness levels were found to relate to higher childbearing desire, wherein those with high happiness show more desire to have children. The factors that influence childbearing desire include economy and finances, various physical, mental, and emotional health aspects, and family experiences among others. Changes in financial stability, relationship status, and happiness levels are factors that may cause initial childbearing desire to change.